Post-apartheid electricity policy and the emergence of South Africa's renewable energy sector - Lucy Baker (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper situates South Africa's new renewable energy sector within the context of the country's electricity system and in turn its unique political economy. I chart major developments in the country's energy policy and governance since the end of apartheid and show how electricity policy is determined by economic, political, and technological factors. I examine the contested negotiation of key policies, which have been fundamental to the introduction of a renewable energy sector. I consider how the new renewable energy sector has evolved thus far and raise key challenges and concerns for its future development.
Keywords: O38; Q28; Q48; 330; South Africa; electricity; renewable energy; political economy; policy